Prognostic Role of IL-18 in Various Human Cancers and Radiation Injuries: A Meta-Analysis - Zhen Yao; Minyan Zhao; Guangyu Gao; Jiawen Yang; Zhenzhen Wang; Yulong Liu (SAGE Publishing, 2020)
Background: In recent years, more and more studies have shown that various inflammatory factors have predictive effects on the prognosis of various human tumors. However, the prognostic role of interleukin 18 (IL-18) remains controversial. Furthermore, its role in radiation-induced injuries relating to radiotherapy (RT) is also unclear. In this study, we conducted the meta-analysis to clarify its roles in prognosis of human tumors and radiation-induced injuries relating to RT. Methods: We comprehensively searched PubMed, Embase, and Cochrane Library to identify studies published before November 2019 involving patients with cancer expressing IL-18 and which reported overall survival (OS) during the follow-up period. Results: A total of 1376 samples from 16 studies showed that high expression of IL-18 is closely related to prognosis and OS for patients with carcinoma (hazard ratio [HR]: 2.12; 95% CI: 1.81-2.49; P = .04; random-effect model). In addition, subgroup analysis proved that high expression of IL-18 was related to poor OS of hematologic tumor (HR: 2.03, 95% CI: 1.44-2.86, P < .00001), hepatocellular carcinoma (HR: 1.99, 95% CI: 1.38-2.86, P = .0002), and gastric cancer (HR: 2.00, 95% CI: 1.12-3.57, P = .02). Conclusions: High expression of IL-18 is related with poor prognosis of carcinoma.